DINAMIKA NAFKAH RUMAH TANGGA PETANI PEDESAAN DENGAN PENDEKATAN SUSTAINABLE LIVELIHOD APPROACII (SLA) (Kasus Petani Tembakau di Lereng Gunung Merapi-Merbabu, Propinsi Jawa Tengah) - Widiyanto Widiyanto; Suwarto Suwarto; Retno Setyowati (AGRITEXTS: Journal of Agricultural Extension, 2010)
The objectives of this research is to understanding poverty from the poorer live, so all of programs to eradicate poverty would consider all of aspects peasant life, social, culture, economy and ecology (holistic view). The background of this research are the failure poverty eradication programs because of uncomprehensive method. This research found there are many vurnerability context which faced by peasant, namely : fluctuation price of tobacco, impact of climate change and limited land (small land) and ecological degradation. In the case, there are five different types of capitals are the tobacco peasant families as disposal, namely : natural capital, physical capital, financial capital, human capital an social capital. The study found that there are many different type of mechanism to respon the vurnerability context, namely: accumulation strategy (large land), consolidation (medium land) and survival (small land). All these strategies (in normal and crisis situation) showed that peasant of this area very flexible mechanism to survive.